An approach from the sociology of the body to social movements - Alexis Patricio Sossa Rojas (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
The present article has as aim articulate two somewhat separate perspectives of the sociological current debate:The sociology of the social movements and the sociology of the body. In this respect, we look to problematized three things. First, why the relevance of the category body, especially the nude, as form and / or resource in the protests. Second, from the thought of Foucault how the social thing interferes in the body, in phenomena as personal as sexuality or family. Finally, from the tensions outlined in section two, we discuss how this gives rise to movements that have claims related to the body, and what theory of social movements is the best to explain it.